2019
DOI: 10.3389/fmolb.2019.00113
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy Is Associated With Dysregulation of Long Non-coding RNAs in the Peripheral Blood

Abstract: Background: Long non-coding RNAs (lncRNAs) are a group of functional transcripts that are not translated to proteins. Recent investigations have underscored their role in the pathogenesis of neurodevelopmental disorders.Methods: In the current investigation, we quantified expression levels of four lncRNAs (HOXA-AS2, SPRY4-IT1, MEG3, and LINC-ROR) in peripheral blood of epileptic patients and normal controls.Results: Expression of HOXA-AS2 was significantly higher in patients compared with controls (Posterior b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…LncRNAs have emerged as regulatory molecules involved in a wide variety of biological processes. A rising number of studies revealed that they were dysregulated during epileptogenesis (Shao et al 2017, Hashemian et al 2019, Villa et al 2019. Interestingly, this current study was the first to investigate the usefulness of serum lncRNAs; BDNF-AS and 17A expressions as diagnostic biomarker of epilepsy.…”
Section: Discussionmentioning
confidence: 78%
“…LncRNAs have emerged as regulatory molecules involved in a wide variety of biological processes. A rising number of studies revealed that they were dysregulated during epileptogenesis (Shao et al 2017, Hashemian et al 2019, Villa et al 2019. Interestingly, this current study was the first to investigate the usefulness of serum lncRNAs; BDNF-AS and 17A expressions as diagnostic biomarker of epilepsy.…”
Section: Discussionmentioning
confidence: 78%
“…An additional study focused on four specific lncRNAs in peripheral blood of patients versus controls (N = 40 per group) -HOXA-AS2, SPRY4-IT1, MEG3, and LINC-ROR. Two out of the four lncRNAs, HOXA-AS2 (Posterior beta = 1.982, P = 0.001) and SPRY4-IT1 (Posterior beta = 1.27, P = 0.02), had increased expression when comparing between patient and control groups [65]. More research is necessary to interpret the use of lncRNAs as an epilepsy biomarker.…”
Section: Lncrnas and Epilepsymentioning
confidence: 97%
“…The study of Hashemian et al considers four specific lncRNAs in the peripheral blood of patients compared to controls (N = 40 per group): HOXA-AS2, SPRY4-IT1, MEG3 and LINC-ROR. In particular, lncRNAs, HOXA-AS2 and SPRY4-IT1 showed greater expression in the comparison between the patient and control groups [ 83 ]. Another study used human peripheral blood from TLE patients and compared the lncRNA ILF3-AS1 levels between serum and hippocampal tissues.…”
Section: Impact On Diagnosis and Prognosismentioning
confidence: 99%